Ratio Decidendi Pemberhentian Sementara Kepala Desa Akibat Dugaan Melakukan Tindak Pidana Pemalsuan Surat - agus suprayitno; Herowati Poesoko; Miftahul Munir (JURNAL HUKUM PELITA, 2025)
This research discusses the court decision with the defendant Akhmad Wa'il as the Head of Guluk Guluk Village, Guluk Guluk District, Sumenep Regency who is suspected of forging letters, namely using fake diplomas when registering as a candidate for village head. Based on the court decision of the Sumenep District Court Number 195/Pid.B/2022/PN.Smp jo 1351/Pid.B/2022/PT. Sby jo 603 K/Pid/2023. In the first and second level verdicts, the judge stated that the defendant was proven to have forged a letter in the form of a fake diploma. However, in the Supreme Court's decision, the defendant was proven not guilty of forging letters, considering that the Supreme Court is the Supreme Court that serves as a Judex Juris and not a Judex Factie. This study aims to describe the ratio of judges in the Supreme Court decision number 603/K/Pid/2023 which annulled the previous decision to not guilty of forging letters. The method used in this study is Normative by using secondary data or library data (library research) with the Statute Approach and Case Study approach